NONNUMERIC ROOTS OF THE ALGEBRAIC EQUATIONS - Hakobian, L. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2007)
The nonnumeric roots of algebraic equations have been investigated here. A relationship between numeric and nonnumeric roots to the algebraic equations of arbitrary order has been established.
Keywords: numeric and nonnumeric roots; relationship; arbitrary order